Al-jabiri's traces in m. amin abdullah's idea about integrative-interconnective paradigm for higher education - Syamsul Kurniawan (ATTARBIYAH: Journal of Islamic Culture and Education, 2020)
Between Islamic science and science, according to M. Amin Abdullah, it should not be dichotomous and lack a strong epistemological basis. For this purpose, the work of "integrating" is not enough, because the problem is the difficulty of combining the disciplines of Islam and science, which sometimes do not get along well and in both there is a potential to crush one another. Therefore, according to him, integration efforts must be followed by interconnection efforts of science. This idea from him emerged after he recontextualized M. Abed Al-Jabiri's thoughts, especially those related to the criticism of Arabic reasoning and the rethinking of epistemology. The results were brilliant. The integrative-interconnective paradigm of Islamic studies in Higher Education which he initiated is considered successful in offering a kind of worldview that is more actual, open, and builds a non-dichotomic scientific bridge in higher education. As developed by UIN Sunan Kalijaga Yogyakarta at this time. This focus is what the author wants to discuss, and for that the author explores mainly all primary literature both written by Abdullah and from the relevant Al-Jabiri, approaches it historically-philosophically and then provides descriptive analysis.